DTS Imaging Improves Lung Nodule Detection with Minimal Dose Increase Compared with CXR - Vinall, Maria (MD Conference Express, 2015)
Digital tomosynthesis (DTS) imaging is a relatively new technique that is increasingly being used for a variety of thoracic indications. This article discusses the results of the GE Healthcare VolumeRAD Lung Nodule Detection Study [NCT00963651], an international, multicenter clinical trial showing that DTS has improved sensitivity for the detection of pulmonary nodules compared with conventional conventional chest x-ray with no loss of specificity and at a similar, minimal radiation level.